Biochar Promotes Nitrogen Transformation and Tomato Yield by Regulating Nitrogen-Related Microorganisms in Tomato Cultivation Soil - Lili Guo; Huiwen Yu; Wenquan Niu; Mourad Kharbach (Agronomy, 2021)
Nitrogen (N) transformation in soil directly determines the effectiveness of N for plant growth. Biochar has received evermore attention because of its significant ability to improve soil. However, the effects of biochar on N-related microorganisms (Lycopersicon esculentum Mill.) in tomato cultivation soil, N transformation, utilisation of water and N fertiliser, and tomato yield remain unclear. The objective of this study was to investigate the responses of N-related microorganisms to biochar and N fertilisation in soil, along with the implications of biochar for altering N transformation, N uptake by tomatoes, and utilisation of water and N fertiliser. A two-year greenhouse experiment containing six biochar levels under drip irrigation (0, 10, 30, 50, 70, and 90 t ha−1) and two N fertiliser application rates (190 and 250 kg ha−1) was conducted in the northwest of China. The results showed that adding biochar significantly promoted urease activity, microbial biomass carbon (MBC), microbial biomass nitrogen (MBN), and the number of amoA-type nitrifiers in the soil. The MBC:N ratio and the number of nirS-type denitrifiers were significantly inhibited when the added amount of biochar was greater than or equal to 30 t ha−1. Moreover, biochar can increase the water content in the soil and can reduce the N lost to leaching. The inorganic N (NO3− and NH4+) in the soil could be better maintained in the rootzone and better absorbed by tomato plants when adding 30, 50, and 70 t ha−1 of biochar. The amount of N fertiliser could be reduced by 24% without a significant loss of tomato yield when the amount of biochar added was over 30 t ha−1. It was indicated that the yield of tomatoes and the net profits were quadratically related to the application rate of biochar. In the test area, 53 t ha−1 of biochar with 190 kg ha−1 of N and 44.6 t ha−1 of biochar with 190 kg ha−1 of N were calculated to be the best amounts from the perspectives of tomato yield and net profit, respectively. Thus, biochar promotes N transformation by regulating N-related microorganisms; hence, it increases the inorganic N in the roots of the plants, reduces N lost to leaching, and significantly promotes the N absorption of tomatoes. The results in this research are of great significance for the development of management strategies for tomato maintenance, environmental protection, and resource conservation.